A material and product audit method for determining the level of quality - Darestani, S. Avakh; M. Y., Ismail; N., Ismail; R. M., Yusuff (Trans Tech Publications, Switzerland, 2011)
This paper introduces a method for evaluating material and product quality. The method is developed based on the normal distribution. For quantitative variable, the method divides the tolerance zones to 3 parts according to normal distribution ±3